13. CLINICAL, PARACLINICAL CHARACTERISTICS IN CHILDREN WITH ALPHA VARIANT OF COVID-19 IN HAI DUONG PROVINCE (Vietnam Journal of Community Medicine, 2023)
Objective: A descriptive study described clinical, paraclinical characteristics in children with theAlpha Variant of COVID-19 in Hai Duong Province. Study subjects and methods: We collected53 children with the Alpha Variant of COVID-19 in Haiduong Province who were admitted fromJanuary to March. Results: Results showed that boys were 54.7%, and the average age was 7.5 ±4.5 years. The most symptom was cough (16%), diarrhea (9.4%), and 77.9% of children with theAlpha Variant of COVID-19 without symptoms. Investigation showed that in 16.9% of patients withthrombocythemia, 15.1% of patients with leukocytosis, 16.9% of patients increase D-dimer in serum,and 13.2% of patients with the increased liver enzyme. In addition, 11.3% of patients had plungelessons on chest X-rays. Conclusion: Clinical, paraclinical characteristics in children with the AlphaVariant of COVID-19 were not severe.
Keywords: Alpha Variant of COVID-19, COVID-19 in children.